Nanoscale Strain Mapping in SIMOX 3-D Sculpted Silicon Waveguides Using Tip-Enhanced Raman Spectroscopy - Huashun Wen; Yuefeng Ji; Bahram Jalali (IEEE Photonics Journal)
Strain in silicon plays a significant role in exploring electro-optical material, boosting transistor performance, tuning birefringence of optical silicon waveguides, and so on. In this paper, we measured, for the first time, the nanoscale strain in the SIMOX 3-D sculpted silicon waveguides using tip-enhanced Raman spectroscopy (TERS). A model, which relates the observed Raman peak shifts to the localized stresses for our TERS experiments, was presented. The tip-induced electric-field enhancements, tip-induced depolarization of incident light, and oblique incidence geometry of the TERS system were included in the model. Both polarizations of incident light and Raman scattered light are selected appropriately with the guidance of the model for obtaining enough electric-field enhancements and accurately calculate the stresses. A 2-D stress map inside the silicon waveguide with spatial resolution of about 20 nm was obtained, and corresponding strains were calculated based on Hooke's law. We observed that the stresses are compressive, and the strains show inhomogeneity. The origins of strain and the strain-induced second-order optical susceptibility inside the SIMOX 3-D sculpted buried silicon waveguides are discussed and analyzed. The mapping of 2-D nanoscale strain and the analysis of second-order optical susceptibility in this work suggest that the SIMOX 3-D sculpted strained silicon might be a potential metamaterial for electro-optical modulation and optical signal processing. Moreover, the presented TERS model could be a valuable tool for probing strain in strained silicon devices.